Back Cover: [UF6]2−: A Molecular Hexafluorido Actinide(IV) Complex with Compensating Spin and Orbital Magnetic Moments (Angew. Chem. Int. Ed. 44/2019). Issue 44 (18th September 2019) - Pedersen, Kasper S.; Meihaus, Katie R.; Rogalev, Andrei; Wilhelm, Fabrice; Aravena, Daniel; Amoza, Martín; Ruiz, Eliseo; Long, Jeffrey R.; Bendix, Jesper; Clérac, Rodolphe
Abstract : Insights into the electronic properties of actinide ions can be obtained by using X‐ray magnetic circular dichroism spectroscopy. In their Communication on page 15650 ff., K. S. Pedersen, R. Clérac, and co‐workers present the first structurally characterized hexafluorido complex of a tetravalent actinide ion, [UF6 ] 2– . Its non‐magnetic ground state results from an almost perfect cancellation of spin and orbital magnetic moments, which are virtually identical in magnitude but opposite in sign.